Kesantunan Berbahasa Santri Putra di Lingkungan Pondok Pesantren Roudlotul Ulum Karangtanjung Alian Kebumen: Kajian Pragmatik - Ibnu Fauzi; Muh. Akbar Kurniawan (Simpati, 2026)
This In the male student community of Pondok Pesantren Roudlotul Ulum Karangtanjung Alian Kebumen, language use reflects a dynamic negotiation of politeness shaped by hierarchical relations and daily social interaction, yet systematic analysis of such politeness practices remains limited. This study aims to describe the forms of compliance and violations of Geoffrey Leech’s Politeness Principle in the daily interactions of male students. A qualitative descriptive approach was employed, using 126 utterances as the data source collected through observation, recording, note-taking, and interviews. The data were analyzed using the extralingual equivalent method based on Leech’s six politeness maxims: tact, generosity, approbation, modesty, agreement, and sympathy. The findings reveal 78 utterances indicating politeness compliance and 48 utterances showing politeness violations. Compliance is predominantly realized in approbation and tact maxims, particularly through expressions of praise, permission requests, and indirect requests. In contrast, violations frequently occur in agreement and approbation maxims, marked by rejection of suggestions and direct criticism among students. The study concludes that politeness practices among male students are context-dependent and fluctuate between adherence to and deviation from politeness norms. These findings contribute to pragmatics by enriching empirical evidence of politeness behavior in pesantren discourse and offer implications for language education in fostering more contextually aware communicative competence.